Polish Concordat 1993 as an instrument of national consensus - DYDUCH, JAN (Prawo Kanoniczne, 2017)
Polish Concordat of 1993 takes into consideration principles of Polish Constitution and Polish laws, as well as the teaching of the Second Vatican Council and the norms of canon law. The central ideas of Concordat are as follows: autonomy, sovereignty of the Catholic Church and Polish Sate and their mutual cooperation. Due to the fact that there is similarity of principles between Concordat and Polish Constitution, the first document in question can create a national consensus and social peace in Poland.